2003
DOI: 10.1590/s0103-64402003000100010
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination in dental unit waterlines

Abstract: The quality of water in a dental unit is of considerable importance because patients and dental staff are regularly exposed to water and aerosol generated from the dental unit. The aim of this study was to evaluate the occurrence of microbial contamination in dental unit waterlines. Water samples were collected aseptically from the waterlines (reservoir, triple-syringe, high-speed) of 15 dental units. After serial dilution to 1:10(6) in APHA, the samples were seeded by the pour-plate technique and cultured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 10 publications
6
28
0
14
Order By: Relevance
“…These figures agree with those reported by Walker et al (30), showing that water supplies of 51% of the dental units in seven European Union countries exceeded the current ADA-recommendations for permissible levels of bacterial contamination. Table 1 also demonstrates that, from forty dental clinics of the city of Barretos, São Paulo, Brazil, in agreement with results reported by Souza-Gugelmin et al (29) the number of P. aeruginosa cells in the water coming from dental equipment was lower than that coming from the water syringe and high-speed drill.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These figures agree with those reported by Walker et al (30), showing that water supplies of 51% of the dental units in seven European Union countries exceeded the current ADA-recommendations for permissible levels of bacterial contamination. Table 1 also demonstrates that, from forty dental clinics of the city of Barretos, São Paulo, Brazil, in agreement with results reported by Souza-Gugelmin et al (29) the number of P. aeruginosa cells in the water coming from dental equipment was lower than that coming from the water syringe and high-speed drill.…”
Section: Resultssupporting
confidence: 90%
“…Costerton et al (10) reported that biofilm fragments dispersed by the municipal water system. Nevertheless, the high percentage of cells counted in handpieces, also reported by Souza-Gugelmin et al (29), should be a convincing indication of the large colonization of the DUWL units by opportunistic pathogens.…”
Section: Resultssupporting
confidence: 58%
“…As classic culture methods for measuring CFUs are only capable of detecting around 5% of the actual total microbial load, the level of contamination in DUWS is considerably worse than the reported figures (Barer and Harwood 1999). On other hand, as Souza-Gugelmin et al (2003) concluded, the use of water with an initial low contamination level did not prevent its increase within DUs. So, high microbiological quality inlet water doesn't warrant a clean DUWS.…”
Section: Discussionmentioning
confidence: 90%
“…32,33 One limitation of the present study is that it presents results for a single dental procedure, prophylaxis with an ultrasonic scaler that has been shown to have a great potential for aerosol generation in the dental office. 1,2,3,4,5,39 However, other dental procedures can also generate a large amount of aerosol with infectious components launched into the dental environment, such as the air turbine handpiece, 6,7 air-water from a three-way syringe 8 and sodium bicarbonate jet. 39 Therefore, one could assume that rinsing with CPC would yield similar benefits if used before the majority of dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The use of certain equipment such as ultrasonic devices, 1,2,3,4,5 highspeed dental handpieces 6,7 or three-way syringes 8 may spread aerosols and splatters containing microorganisms in the environment. These microorganisms may cause cross-infections in the dental office, jeopardizing the health of patients and dental professionals.…”
Section: Introductionmentioning
confidence: 99%